Exploring NICU Nurses' Affective Responses to End-of-Life Care. (April 2017) - Lewis, Stephanie Lacefield
Abstract : Background: The survival rate for infants born with life-threatening problems has improved greatly over the last few decades. Nevertheless, infants still die in neonatal intensive care units (NICUs) every day. Despite existing standards of care, some aspects of end-of-life care (EOLC) are still not delivered consistently. Little is known about how NICU nurses' individual experiences affect EOLC. Purpose: The purpose of this study was to explore, through lived and told stories, the affective, interactional, and meaning-related responses that NICU nurses have while caring for dying infants and their families. Coping strategies and changes in practice were also explored. Methods: Thirty-six members of the National Association of Neonatal Nurses submitted written narratives about an EOLC experience during which the nurse experienced strong emotions. Findings: Narrative analysis revealed many affective responses, but 3 were the most frequent: responsibility, moral distress, and identification. Coping methods included healthy and less healthy strategies, such as colleague support, informal and formal debriefing, practicing intentional gratefulness, avoidance, and compartmentalization. Changes in practice identified were universally described as professional growth through the use of reflective practice. Implications for Practice & Research: Educators should discuss the range of emotions experienced by caregivers related to EOLC and healthy coping strategies and encourage the use of reflective practice as a facilitator of professional growth. Nurse leaders should promote supportive environments in NICUs and ensure debriefing opportunities for nurses who have recently cared for a dying infant. Future research should focus on formulating interventions to utilize debriefing with NICU nurses and perhaps the development of EOLC mentors.